STRATEGI PENGEMBANGAN KINERJA PERIZINAN USAHA PENANGKAPAN IKAN - Shinta Yuniarta; Sugeng Hari Wisudo; Budhi Hascaryo Iskandar (Buletin PSP, 2011)
Directorate Fisheries Business License is a regulator for fishing business license of fishing vessel more than 30 GT and/or 90 HP machine power and over 12 mils sea operations area. The implementation of fishing business license based on the decree of Minister of Marine Affairs Fisheries number PER.05/MEN/2008 and number PER.12/MEN/2009. These regulations are a tool to fullfill fishing business necessity. Therefore, it is important to design a development performance strategy of fisheries business license. The design, using Balanced Scorecard approach, based on 4 perspectives, there are learning and growth, internal business processes, financial and customers (Kaplan and Norton 2000, Gaspersz 2002, Niven 2003). Those strategies are expected to be long term objectives. These objectives divided into 4 perspectives. All the objectives have cause and effect linkages and designed into strategic map for Directorate Fisheries Business License. Each of these objectives has standards, targets and initiatives in order to achieve the objectives and targets too.